Cumulative childhood trauma and cybervictimization among Chinese college students: Internet addiction as a mediator and roommate relationships as a moderator - Xie, Yunzi; Wu, Jixia; Zhang, Chen; Zhu, Lingyi (Frontiers in Psychology, 2022)
Existing studies have found that childhood trauma is a risk predictor of cybervictimization, but few studies have explored the relationship between cumulative childhood trauma and college students' cybervictimization. This study explored the relationship and the roles of Internet addiction and Internet victimization between them. A total of 854 college students (568 females, Mage = 18.92 years old, SD = 0.86) completed a survey including the Short Form of Childhood Trauma Questionnaire, the Cyberbullying Inventory, the Young’s Internet Addiction scale and the revised Roommate Relationships Questionnaire. The results showed that: (1) cumulative childhood trauma was significantly positively associated with cybervictimization; (2) Internet addiction played a mediating role between cumulative childhood trauma and cybervictimization; and (3) roommate relationships played a moderating role between cumulative childhood trauma and cybervictimization, as well as Internet addiction and cybervictimization. The research findings provide a theoretical and practical basis for the prevention and intervention of college students' cybervictimization.